2012
DOI: 10.1111/j.1533-2500.2012.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Approach for the Management of Hunan Hand Syndrome: A Case Report

Abstract: Hunan hand syndrome, a form of painful contact dermatitis, is a rare case finding. It is usually seen in people with continuous and prolonged exposure to chili peppers. The main ingredient in chili peppers is capsaicin that leads to the clinical condition, Hunan hand syndrome. This is paradoxical to the use of capsaicin as local application for relief of pain in various clinical situations, such as diabetic neuropathy and postherpetic neuralgia. We report a case of Hunan hand syndrome, managed successfully by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…(Chi sq = 24.32, df= 1, p < 0.001 It shows the there is a significant increase in the respiratory, skin and eye related problems. There is an increase in the respiratory problems such as cough arising due to the handling of the chili powder is also supported by some other studies 18 . The origin of any respiratory problem can be traced to the effect of the fine particulate matter in the development of the COPD.…”
Section: Methodssupporting
confidence: 59%
“…(Chi sq = 24.32, df= 1, p < 0.001 It shows the there is a significant increase in the respiratory, skin and eye related problems. There is an increase in the respiratory problems such as cough arising due to the handling of the chili powder is also supported by some other studies 18 . The origin of any respiratory problem can be traced to the effect of the fine particulate matter in the development of the COPD.…”
Section: Methodssupporting
confidence: 59%
“…If the reaction is severe and persistent, a continuous stellate ganglion block may alleviate the pain of capsaicin-induced contact dermatitis. 9…”
Section: Obtaining Reliefmentioning
confidence: 99%
“…It also is used to treat diabetic neuropathy, 5 postherpetic neuralgia, 6 psoriasis, 16 and other conditions. Studies have shown that capsaicin might be useful in treating trigeminal neuralgia, 17 fibromyalgia, 18 migraines, 14 cluster headaches, 9 and HIV-associated distal sensory neuropathy. 5 Delivery of Capsaicin-Capsaicin preferentially acts on C-fibers, which transmit dull, aching, chronic pain.…”
Section: Medicinal Usementioning
confidence: 99%